2021
DOI: 10.1038/s41380-021-01328-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type- and region-specific modulation of cocaine seeking by micro-RNA-1 in striatal projection neurons

Abstract: The persistent and experience-dependent nature of drug addiction may result in part from epigenetic alterations, including non-coding micro-RNAs (miRNAs), which are both critical for neuronal function and modulated by cocaine in the striatum. Two major striatal cell populations, the striato-nigral and striato-pallidal projection neurons, express, respectively, the D1 (D1-SPNs) and D2 (D2-SPNs) dopamine receptor, and display distinct but complementary functions in drug-evoked responses. However, a cell-type-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Long non-coding RNAs have been divided into several classes based on their genomic position in relation to coding genes, which aids in predicting some of their potential mode of action in modulating other cellular RNA molecules ( 22 ). Based on this classification, DElncRNAs in the morphine group compared to the saline group were discovered to be 52% ( 16 ) intergenic, 26% ( 8 ) natural antisense, 19% ( 6 ) intronic antisense regions and 3% ( 1 ) sense ( Figure 3D ) in the genome. Like proteins, the function of lncRNAs is dependent on their subcellular localization ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long non-coding RNAs have been divided into several classes based on their genomic position in relation to coding genes, which aids in predicting some of their potential mode of action in modulating other cellular RNA molecules ( 22 ). Based on this classification, DElncRNAs in the morphine group compared to the saline group were discovered to be 52% ( 16 ) intergenic, 26% ( 8 ) natural antisense, 19% ( 6 ) intronic antisense regions and 3% ( 1 ) sense ( Figure 3D ) in the genome. Like proteins, the function of lncRNAs is dependent on their subcellular localization ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among various epigenetic processes, attention has recently been focused on non-coding RNAs (ncRNAs), including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), which play a important role in various biological functions. Forget et al reported that the overexpression of miR1 in dorsal striatum D1-striato-pallidal projection neurons reduced cocaine-induced CPP reinstatement ( 8 ). LncRNAs are a class of non-coding transcripts over 200 nt long ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that ICuRuS generated robust and reproducible H3K4me3 and H3K27me3 profiles at sufficient depth to examine cell-type specific chromatin from a single mouse striatum. These findings are an improvement over current methods, such as bulk tissue CnR 7,40 , which obscures cell-type specificity, and single-cell CnR, which requires pooled brain tissue and obscures subject variability 4,5 , a critical barrier given individual differences in stimulus-induced gene expression and susceptibility to psychiatric disease 33,5052 . Recent studies have applied FACS to isolate MSNs, but we found that the affinity purification strategy used in ICuRuS (and in the original INTACT protocol 9 ) potentially avoids FACS induced ectopic upregulation of activity dependent genes 5355 .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it is already known that passive cocaine administration in the NAc of mice induces changes in the expression levels of several miRNAs compared with saline‐injected mice revealing an intrinsic cocaine pharmacological effect that has been discarded considering the experimental conditions chosen in our study. 57 Indeed, the putative expression changes observed when comparing the saline group versus cocaine mice could be driven by the direct pharmacological effect of cocaine in the brain and not necessarily by the molecular adaptations that underlie resilience or vulnerability. Differentially expressed miRNAs were not identified in the first global comparison between mice resilient and vulnerable to cocaine addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the differential miRNA expression found between groups was not due to a differential pharmacological effect of cocaine and was therefore related to the different behavioural phenotypes of both groups. Indeed, it is already known that passive cocaine administration in the NAc of mice induces changes in the expression levels of several miRNAs compared with saline‐injected mice revealing an intrinsic cocaine pharmacological effect that has been discarded considering the experimental conditions chosen in our study 57 . Indeed, the putative expression changes observed when comparing the saline group versus cocaine mice could be driven by the direct pharmacological effect of cocaine in the brain and not necessarily by the molecular adaptations that underlie resilience or vulnerability.…”
Section: Discussionmentioning
confidence: 99%